HLA genetic diversity in Hungarians and Hungarian Gypsies: complementary differentiation patterns and demographic signals revealed by HLA‐A, ‐B and ‐DRB1 in Central Europe. Issue 2 (7th July 2015) - Inotai, D.; Szilvasi, A.; Benko, S.; Boros‐Major, A.; Illes, Z.; Bors, A.; Kiss, K. P.; Rajczy, K.; Gelle‐Hossó, A.; Buhler, S.; Nunes, J. M.; Sanchez‐Mazas, A.; et al.
Abstract Systematic analyses of human leukocyte antigen (HLA) profiles in different populations may increase the efficiency of bone marrow donor selection and help reconstructing human peopling history. We typed HLA‐A, ‐B, and ‐DRB1 allele groups in two bone marrow donor cohorts of 2402 Hungarians and 186 Hungarian Gypsies and compared them with several Central‐European, Spanish Gypsy, and Indian populations. Our results indicate that different European Gypsy populations share a common origin but diverged genetically as a consequence of founder effect and rapid genetic drift, whereas other European populations are related genetically in relation to geography. This study also suggests that while HLA‐A accurately depicts the effects of genetic drift, HLA‐B, and ‐DRB1 conserve more signatures of ancient population relationships, as a result of balancing selection.